A Convenient Synthesis of Benzo [h] Cyclopenta [b] [1,6]-Naphthyridin-6(5H)Ones - ARUL PRAKASH, G.; RAJENDRAN, S.P. (Asian Journal of Chemistry, 2010)
Substituted benzo[h]cyclopenta[b][1,6]naphtbyridin-6(5H)ones (2) have been synthesized by the condensation of 4-amino-3- formylquinoline-2(1H)ones (1) with cyclopentanone in presence of acetic acid and sulphuric acid.